Fall in the prevalence of chronic gastritis over 15 years: analysis of outpatient series in Finland from 1977, 1985, and 1992. Issue 9 (September 1994) - Sipponen, P; Helske, T; Järvinen, P; Hyvärinen, H; Seppälä, K; Siurala, M
Abstract : To investigate whether the occurrence of chronic gastritis (and Helicobacter pylori acquisition) has changed in Finland in the past 15 years, the prevalence rates of chronic gastritis in biopsy specimens in consecutive series of outpatients (aged 20 or more) who had undergone diagnostic upper gastrointestinal endoscopy in 1977 (702 patients), 1985 (1309 patients), or 1992 (1447 patients) were compared. The prevalences of gastritis in these series were also compared with that in a random sample (438 subjects) of people who underwent endoscopy in 1974-76. It seemed that the prevalence of gastritis was significantly lower in the outpatients in 1992 than in the random endoscopy sample in 1974-76. The reduction was most noticeable in young age groups (20-49 years) in which the decline was 38% (drop from 66% to 41%). In addition, it seemed that the prevalence of gastritis was very dissimilar in different birth cohorts. The prevalence was high (70-80%) in 1977, 1985, and 1992 in the cohorts born at the beginning of the century and lower (40-50%) in those born during later decades. The prevalence rates had remained unchanged in the same cohorts over the 15 years (from 1977 to 1992) suggesting that the people had mainly been infected with H pylori and contracted gastritis before the age of 20. In conclusion, gastritis is a cohort phenomenon and its prevalence has fallen in Finland in the last 15 years. This decrease is caused by a decline of the rate of H pylori acquisition in birth cohorts, particularly in childhood and adolescence (below age of 20).